Genetic variants in the CPNE5 gene are associated with alcohol dependence and obesity in Caucasian populations. (December 2015) - Wang, Ke-Sheng; Zuo, Lingjun; Pan, Yue; Xie, Changchun; Luo, Xingguang
Abstract: Alcohol addiction may increase the risk of obesity due to shared genetic components. The Copine V (CPNE5) gene is involved in Ca 2+ binding and may play an important role in the development of the central nervous system. This study tested the genetic associations of 77 single-nucleotide polymorphisms (SNPs) within the CPNE5 gene with alcohol dependence (AD) and obesity using a Caucasian sample – The Study of Addiction – Genetics and Environment (SAGE) sample (1066 AD cases and 1278 non-AD controls, 422 obese cases and 1395 non-obese controls). The Marshfield sample (1442 obese cases and 2122 non-obese controls) was used for replication of obesity. Multiple logistic regression analysis was performed using the PLINK software. In the SAGE sample, we identified 10 SNPs associated with AD and 17 SNPs associated with obesity (p < 0.05). Interestingly, 6 SNPs (rs9986517, rs9470387, rs3213534, rs10456444, rs3752482, and rs9470386) were associated with both AD (OR = 0.77, 0.77, 0.83, 0.84, 0.79 and 1.14, respectively; p = 9.72 × 10 −5, 1.1 × 10 −4, 4.09 × 10 −3, 5.26 × 10 −3, 1.59 × 10 −2, and 3.81 × 10 −2, respectively) and obesity (OR = 0.77, 0.77, 0.78, 0.77, 0.68 and 1.18, respectively; p = 2.74 × 10 −3, 2.69 × 10 −3, 2.45 × 10 −3, 1.01 × 10 −3, 5.18 × 10 −3 and 3.85 × 10 −2, respectively). In the Marshfield sample, rs3752480 was associated with obesity (p = 0.0379). In addition, four SNPs (rs9986517, rs10456444, rs7763347 and rs4714010) showed associations with obesity in the meta-analysis using both samples (p = 0.00493, 0.0274, 0.00346, and 0.0141, respectively). These findings provide the first evidence of common genetic variants in the CPNE5 gene influencing both the AD and obesity; and will serve as a resource for replication in other populations. Graphical abstract: log(p) values of alcohol dependence and obesity for 6 SNPs. Highlights: 10 SNPs in CPNE5 associated with alcohol dependence (AD) and 12 SNPs with obesity. The most significant SNP associated with AD was rs998617 with p = 9.72 × 10 −5 . The most significant SNP associated with obesity was rs10456444 with p = 1.01 × 10 −3 . 6 SNPs associated with both AD and obesity in the Marshfield sample. Calcium (Ca 2+ ) may be one of the mechanisms linking between AD and obesity.